A mononuclear nickel(II) complex based on polypyridyl ligand: synthesis, characterization, and biological activity. Issue 3 (1st February 2016) - Ouyang, Yan; Zhao, Xiao-Fei; Qiao, Xin; Zhang, Ran; Bao, Wei-Guo; Xie, Cheng-Zhi; Xu, Jing-Yuan
Abstract: [Ni(acac)2 ( o -NPIP)](CH3 OH)3 (acac = acetylacetonate), based on the polypyridyl ligand 2-(2-nitrophenyl)imidazo[4, 5-f]1, 10-phenanthroline) ( o -NPIP), has been synthesized and characterized by single-crystal analysis, IR and electronic spectra. In the structure of Ni(II) complex, the coordination sphere around Ni(II) is distorted octahedral with one o -NPIP and two acetylacetonates. DNA binding and human serum albumin (HSA) interactions with the Ni(II) complex have been investigated by electronic absorption and fluorescence measurements, revealing that the Ni(II) complex binds with DNA via intercalative binding. The quenching constants verified a dynamic quenching mechanism between HSA and the Ni complex by fluorescence quenching. ΔG, ΔH, and ΔS at different temperatures (288, 298, and 310 K) indicated that hydrophobic interactions play a major role. Synchronous fluorescence spectral experiments revealed that the Ni(II) complex affected the microenvironment around the tryptophan residue of HSA. Abstract :